2011
DOI: 10.1590/s1806-66902011000300028
|View full text |Cite
|
Sign up to set email alerts
|

Elaboração e validação da escala diagramática para avaliação da mancha branca do milho

Abstract: Resumo -A correta avaliação das doenças de plantas é de fundamental importância para os estudos epidemiológicos e para as estratégias de controle das mesmas. A escala diagramática de doenças além de contribuir para a correta avaliação fornece um padrão de uniformidade aos diferentes avaliadores. O objetivo deste trabalho foi desenvolver e validar a escala diagramática para quantificação da severidade da Mancha Branca em folhas de milho. Para a construção da escala, utilizaram-se os limites de severidade mínima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 7 publications
0
9
0
5
Order By: Relevance
“…Using the PPD scale, the evaluators improved the accuracy levels for severity estimates, as observed by other authors who evaluated dendrophama blight in strawberry (Mazaro et al, 2006), gray mold in castor bean (Sussel et al, 2009), and maize white spot (Malagi et al, 2011). Some studies have shown some variability among evaluators using the same scale; therefore, assessments of accuracy and precision are greatly influenced by the ability of each evaluator to estimate the inherent severity (Nutter Jr. & Schultz, 1995), and can be affected by factors such as the complexity of the severity to be assessed, as for cassava, and as the different types of PPD in their shapes and colors.…”
Section: Resultsmentioning
confidence: 67%
“…Using the PPD scale, the evaluators improved the accuracy levels for severity estimates, as observed by other authors who evaluated dendrophama blight in strawberry (Mazaro et al, 2006), gray mold in castor bean (Sussel et al, 2009), and maize white spot (Malagi et al, 2011). Some studies have shown some variability among evaluators using the same scale; therefore, assessments of accuracy and precision are greatly influenced by the ability of each evaluator to estimate the inherent severity (Nutter Jr. & Schultz, 1995), and can be affected by factors such as the complexity of the severity to be assessed, as for cassava, and as the different types of PPD in their shapes and colors.…”
Section: Resultsmentioning
confidence: 67%
“…; Malagi et al. ; Sachs et al. ), there is limited evidence whether coloured diagrams are superior to black and white drawings in regard to accuracy and reliability of estimates (Angelotti et al.…”
Section: Introductionmentioning
confidence: 99%
“…Although image analysis tools have fostered the development of disease diagrams with enhanced realism (Bock et al 2010), most of disease diagrams reported to date are simple drawings of leaves in two contrasting colours such as black (for the diseased area) and white (for the healthy area). While some are represented with images of actual leaves in true colour (Halfeld-Vieira and Nechet 2006;Salgado et al 2009;Soares et al 2009;Malagi et al 2011;Sachs et al 2011), there is limited evidence whether coloured diagrams are superior to black and white drawings in regard to accuracy and reliability of estimates (Angelotti et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…These scales can be used to standardize the severity estimation and reduce the subjective of disease severity visual estimates. The diagrammatic scales is expected to be easy and quick for a wide range of conditions with reproducible, accurate, and precise results (MALAGI et al, 2011;SACHS et al, 2011;SANTOS et al, 2011;YADAV et al, 2012). Accuracy refers to how faithful an estimate is from the actual amount of the evaluated disease, while precision corresponds to the confi dence and/or repeatability associated to such estimate (NUTTER JR. & SCHULTZ, 1995, ANGELOTTI et al, 2008MICHEREFF et al, 2009).…”
Section: Introductionmentioning
confidence: 99%